Group III-Sb Metamorphic Buffer on Si for p-Channel all-III-V CMOS: Electrical Properties, Growth and Surface Defects. Issue 1790 (2015) - Sasaki, Shun; Madisetti, Shailesh; Tokranov, Vadim; Yakimov, Michael; Hirayama, Makoto; Bentley, Steven; Galatage, Rohit; Jacob, Ajey P.; Oktyabrsky, Serge
ABSTRACT: Group III-Sb compound semiconductors are promising materials for future CMOS circuits. Especially, In1-x Gax Sb is considered as a complimentary p-type channel material to n-type In1-x Gax As MOSFET due to the superior hole transport properties and similar chemical properties in III-Sb's to those of InGaAs. The heteroepitaxial growth of In1-x Gax Sb on Si substrate has significant advantage for volume fabrication of III-V ICs. However large lattice mismatch between InGaSb and Si results in many growth-related defects (micro twins, threading dislocations and antiphase domain boundaries); these defects also act as deep acceptor levels. Accordingly, unintentional doping in InGaSb films causes additional scattering, increase junction leakages and affects the interface properties. In this paper, we studied the correlations between of defects and hole carrier densities in GaSb and strained In1-x Gax Sb quantum well layers by using various designs of metamorphic superlattice buffers.